Perceived Realism: Dimensions and Roles in Narrative Persuasion. (August 2014) - Cho, Hyunyi; Shen, Lijiang; Wilson, Kari
Perceived realism may be a crucial message characteristic facilitating narrative-based persuasion. This study examined dimensions of perceived realism and their roles in narrative persuasion. Data based on responses to messages on three topics showed that perceived realism was multidimensional. Its dimensions included plausibility, typicality, factuality, narrative consistency, and perceptual quality. Plausibility predicted emotional involvement, but not identification. Typicality predicted identification, but not emotional involvement. Narrative consistency and perceptual quality predicted message evaluation. Emotional involvement, identification, and message evaluation, in turn, predicted attitudes. Implications for theory, research, and message design pertinent to narrative persuasion are discussed.